Parametric modeling of a solid state Ericsson cycle heat engine. (1st December 2021) - Miller, Timothy F.
Abstract: The Johnson Thermoelectric Converter (JTEC) operates as an approximation of an Ericsson cycle thermodynamic heat engine with no moving parts. During operation, hydrogen flows from a high-temperature high-pressure region to a low-pressure region by way of a membrane-electrode assembly. In passing through the assembly, the hydrogen is stripped of its electrons which flow through the circuit and reform with protons to the recover hydrogen on the low-pressure side. Some of the electrical power extracted is used to electrochemically "pump" the hydrogen back to the low-temperature high-pressure side and sustain the pressure differential. The objective of the work presented here was to mathematically characterize a JTEC system and to develop the coupled relationships between design goals like efficiency, net power production, and power density; and design parameters like high versus low operating temperatures and pressures, device geometry, and thermophysical properties of the device materials and working fluid. Power production is related to the operating pressure ratio, the ratio of high to low device operating temperatures, the high operating temperature, and the effective heat transfer area of the hot end. The efficiency is related to several non-dimensional and dimensional number groups (especially the recuperator effectiveness). The power density or volume of the device is related to a different recuperator parameter, the high temperature of the heat addition source, the cold temperature of the thermal rejection source, and the internal device geometry. Even with reasonable simplifications and assumptions, the design space contains a large number of variable parameters. The model equations were exercised over the large parametric trade space. Highlights: Parametric study of a solid state Ericsson heat engine was performed. Good recuperator design was the greatest contributor to cycle efficiency. Power was most impacted by ratio of device surface area to ion exchange thickness.